Validating Use-Cases with the AsmL Test Tool - Schulte, Wolfram; Tillmann, Nikolai; Veanes, Margus; Barnett, Mike (QSIC, 2003)
The Abstract State Machine Language supports use-case oriented modeling in a faithful way. In this paper we discuss how the AsmL test tool, a new component of the AsmL tool environment, is used to generate finite state machines from use-case models which can be used for validation purposes or for testing.